O direito à adequada e racional valoração da prova : o livre convencimento nas decisões do Superior Tribunal de Justiça e o direito fundamental a uma decisão fundamentada - Figueira, Yasmin Shiguematsu Varjão (2023)
The theme of this paper is the rational valuation of proof in light of the idea of the liberty of motivated conviction as the basis for judicial decisions, particularly in rulings issued by the Superior Court of Justice, under the perspective of procedural constitutional principles of contradictory and due process as indispensable prerequisites for guaranteeing the fundamental right to a constitutionally fair trial. The research will be conducted based on selected decisions concerning the liberty of conviction as an adequate and sufficient means to consider a decision justified, and it seeks to answer the following question: How does liberty of conviction as a sufficient foundation in evidentiary matters reflect on the constitutional guarantee of contradictory within the procedural scope? And, therefore, going from the decisions issued by the Superior Court of Justice intends to comprehend what are the possible models of determination that could serve as parameters for a rational valuation of proof enabling judicial control over decisions regarding evidence. The study was based on three hypotheses: that "free" conviction alone would not suffice as a basis for a judicial decision in a collaborative process; that the term "free" would invoke a subjective freedom that would make evidentiary reasoning unattainable to the parties; and finally, that the use of evidentiary standards would ensure access to the reasons for decisions, as well as compliance with the duty to provide reasoning for judicial rulings. At the end of this study, it was concluded that the existence of evidentiary standards would translate freedom in assessment into objective freedom, allowing the parties to become aware of the reasons that motivated the judicial decision, ensuring judicial control over matters of evidence, and the constitutional guarantee of a properly reasoned decision.